2020
DOI: 10.1002/mrm.28327
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐learned short tau inversion recovery imaging using multi‐contrast MR images

Abstract: Purpose To generate short tau, or short inversion time (TI), inversion recovery (STIR) images from three multi‐contrast MR images, without additional scanning, using a deep neural network. Methods For simulation studies, we used multi‐contrast simulation images. For in‐vivo studies, we acquired knee MR images including 288 slices of T1‐weighted (T1‐w), T2‐weighted (T2‐w), gradient‐recalled echo (GRE), and STIR images taken from 12 healthy volunteers. Our MR image synthesis method generates a new contrast MR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…This may be based on the fact that both T1 and T2 images contain independent information [ 23 ]; combining those naturally leads to an increase in information for different pathologies. To date, the only publication that combines T1 and T2 to generate a STIR sequence using deep learning was recently published by Kim et al [ 24 ]. With only 12 healthy volunteers, this study demonstrated that deep learning can be used to generate real-looking STIR images of a knee MRI.…”
Section: Discussionmentioning
confidence: 99%
“…This may be based on the fact that both T1 and T2 images contain independent information [ 23 ]; combining those naturally leads to an increase in information for different pathologies. To date, the only publication that combines T1 and T2 to generate a STIR sequence using deep learning was recently published by Kim et al [ 24 ]. With only 12 healthy volunteers, this study demonstrated that deep learning can be used to generate real-looking STIR images of a knee MRI.…”
Section: Discussionmentioning
confidence: 99%
“…An example synthetic fat-saturated image from this study can be seen in Figure 4A. In a similar application, Kim et al 61 trained a neural network to generate synthetic STIR images from multiple input images (ie, T1w and T2w TSE images and 1 gradient-recalled echo image). With training data from 12 subjects, they found that they can produce synthetic STIR images that resemble an actual acquired STIR image (see Fig.…”
Section: Synthetic Mri Methodsmentioning
confidence: 97%
“…133 For synthesizing a short inversion time inversion recovery (STIR) image, a DNN approximated a function which produced a STIR image from T1-weighted, T2-weighted, and gradient-recalled echo images. 134 As a part of a T2 mapping method, ANNs approximated functions that produced a T2weighted image for several types of tissues from a T1weighted image. 135…”
Section: Image Synthesismentioning
confidence: 99%